Prevalence of hypertension in china: a cross-sectional study. - Yun Gao (Public Library of Science (PLoS), 2013)
Aims The present study aimed to assess the prevalence of hypertension among Chinese adults. Methods Data were obtained from sphygmomanometer measurements and a questionnaire administered to 46239 Chinese adults ≥20 years of age who participated in the 2007-2008 China National Diabetes and Metabolic Disorders Study. Hypertension was defined as blood pressure ≥140/90 mm Hg or use of antihypertensive medication. Results A total of 26.6% of Chinese adults had hypertension, and a significantly greater number of men were hypertensive than women (29.2% vs 24.1%, p<0.001). The age-specific prevalence of hypertension was 13.0%, 36.7%, and 56.5% among persons aged 20 to 44 years (young people), 45 to 64 years (middle-aged people), and ≥65 years (elderly people), respectively. In economically developed regions, the prevalence of hypertension was significantly higher among rural residents than among urban residents (31.3% vs 29.2%, p = 0.001). Among women or individuals who lived in the northern region, the disparity in the prevalence of hypertension between urban and rural areas disappeared (women: 24.0% vs. 24.0%, p = 0.942; northern region: 31.6% vs. 31.2%, p = 0.505). Among hypertensive patients, 45.0% were aware of their condition, 36.2% were treated, and 11.1% were adequately controlled. Conclusions The prevalence of hypertension in China is increasing. The trend of an increase in prevalence is striking in young people and rural populations. Hypertension awareness, treatment, and control are poor. Public health efforts for further improving awareness and enhancing effective control are urgently needed in China, especially in emerging populations.